Pengaruh Good Corporate Governance dan Kebijakan Dividen terhadap Kinerja Keuangan - Oktavira, Yolanda; Taqwa, Salma; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to prove and analyze the influence of good corporate governance and dividend policy on company financial performance. This research was conducted on insurance sub-sector companies on the Indonesia Stock Exchange. The data used is from 2017 to 2021. In this study, company performance is measured by Tobin's Q, while good corporate governance is measured by managerial ownership, size of the board of directors and audit committee. Apart from that, another variable used in this research is dividend policy. The data analysis technique used is multiple regression (OLS) and t-statistical testing. Based on the results of hypothesis testing, it was found that managerial ownership and dividend policy had a positive effect on company performance, while the size of the board of directors and audit committee had no effect on the financial performance of insurance sub-sector companies on the Indonesia Stock Exchange.